1997
DOI: 10.1046/j.1365-2818.1997.d01-629.x
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative comparison of image restoration methods for confocal microscopy

Abstract: SummaryIn this paper, we compare the performance of three iterative methods for image restoration: the Richardson-Lucy algorithm, the iterative constrained Tikhonov-Miller algorithm (ICTM) and the Carrington algorithm. Both the ICTM and the Carrington algorithm are based on an additive Gaussian noise model, but differ in the way they incorporate the non-negativity constraint. Under low light-level conditions, this additive (Gaussian) noise model is a poor description of the actual photon-limited image recordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
115
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(115 citation statements)
references
References 17 publications
0
115
0
Order By: Relevance
“…In the case of noiseless measurements, we would get two identical results. [4]. However, these methods are limited by the additional assumptions, e.g.…”
Section: Materials and Current Methodsmentioning
confidence: 99%
“…In the case of noiseless measurements, we would get two identical results. [4]. However, these methods are limited by the additional assumptions, e.g.…”
Section: Materials and Current Methodsmentioning
confidence: 99%
“…In our work we propose to classify used methods in four classes: linear, nonlinear, statistical, and blind methods. The first class concerns the linear methods, like Wiener [10,11] filter or that of Tikhonov-Miller [13,23]. To decrease the sensitivity to noise of the inverse filter and its singularities, the Wiener filter minimizes the mean square error between the original image and the restored one.…”
Section: Restoration Methodsmentioning
confidence: 99%
“…In the past few years, large progress has been made in the field of image restoration (Carrington et al, 1995;Van Kempen et al, 1997;Verveer and Jovin, 1998). Furthermore, it has been shown that iterative image restoration can be successfully combined with 4Pi-confocal microscopy, resulting in an even higher 3D resolution .…”
Section: Image Deconvolution and Restoration In 4pi-confocal Microscopymentioning
confidence: 99%